(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The inability of a couple to conceive after a year of unprotected sexual activity is known as infertility. In Pakistan, infertility is 21.9% of the population. Polycystic ovarian syndrome (PCO) is the most prevalent cause of infertility that can be treated medically. The purpose of this study was to determine the prevalence of PCO-related infertility and the results of treatment for infertile couples who visited Gynecology department Divisional Headquarters Teaching Hospital Mirpur ajk. Methods: Gynecology department Divisional Headquarters Teaching Hospital Mirpur ajk hosted this prospective observational study for three months, from aug to oct 2023. This study covered 160 infertile couples in total. Result: 37.5% of female-related infertility cases had PCOs. Other reasons of infertility in women included endometriosis (9.3%), hyperprolactenemia (1.8%), hypothyroidism (1.25%), and pelvic inflammatory illness (43.7%). Various forms of treatment were administered to PCOS patients. 58.3% of the 160 PCO patients who received clomephene citrate for ovulation induction became pregnant. A combination of metformin and clomephene citrate was administered to TWENTY women. 13 of them (65%) became pregnant. Two (40%) of the five patients who received gonadotrophins became pregnant. TWO (20%) of the 10 patients who had laparoscopic drilling became pregnant. Conclusion: Contrary to the literature research, the second most common cause of infertility in women was found to be polycystic ovarian syndrome. However, as evidenced by the global literature, it had excellent results following medical and/or surgical intervention.